Transformasi Nilai-Nilai Luhur Dalam Lontar Dharma Śāsana Sebagai Fondasi Pendidikan Sasana Hindu Di Era Modern - Ariyoga, I Nyoman (Jayapangus Press, 2025)
The background of this study stems from the gap between the rich spiritual and moral values found in the Lontar Dharma Śāsana a treasured body of Balinese Hindu literature and its pedagogical implementation in contemporary formal education, where the text is often limited to ritualistic studies without transformative integration into character formation. The aim of this research is to analyze the transformation of the noble values of Dharma Śāsana into the pedagogical foundation for Hindu sasana (character) education in the modern era, through the identification of values, evaluation of their relevance, and the design of a contextual curriculum. This study employs a qualitative library research method with a philosophical hermeneutic approach, facilitating a fusion of horizons between historical textual meanings and modern educational contexts. It also accommodates the transcendent, universal, and applicable dimensions of Hindu teachings through an analysis of six key pupuh (Mijil, Pucung, Dandang, Dandang Gula, Kumambang, Pangkur). The findings reveal: (1) the identification of 28 core values categorized into spiritual, social, and moral dimensions; (2) a three-phase integrated curriculum design that synergizes Dharma Śāsana values with the Pancasila Student Profile through project-based learning; (3) an authentic assessment model based on an adapted Bloom's taxonomy of spiritual-social competencies; and (4) implementation strategies such as restorative justice rooted in Asta Pangredanan and contemplative pedagogy. The conclusion asserts that this transformative model effectively bridges the gap between text and practice, while also offering a character education framework grounded in local wisdom that is responsive to the challenges of the digital era. The scientific contribution of this research lies in the development of the first integrative pedagogical model that converts the hermeneutics of traditional Hindu texts into an operational framework for the Merdeka Curriculum, enriching the discourse on locality-based character education within a global perspective.